Thyroid hemiagenesis with compensatory hypertrophy of the remaining lobe: A case report - Abdullah Unar, Ambreen; Akhtar, Shabbir; Khalid Ghaloo, Shayan; Awan, Muhammad Ozair; Anjum, Saba (Journal of the Pakistan Medical Association, 2024)
Thyroid hemiagenesis is defined as a failure of one thyroid lobe development. This condition predominantly manifests as an incidental finding during radiological investigation. This paper reports the case of a 53-year-old female, a known case of hypertension, who visited the ENT clinic at AKU, a tertiary care centre in Karachi, Pakistan. The patient presented with hemiagenesis of the right thyroid lobe with enlargement of the contralateral lobe resulting in airway compression. She was subjected to excision of the thyroid gland without any intra-operative or postoperative complications. There were no complaints of dyspnoea, stridor or hoarseness during the hospital stay. The patient was discharged and was found to be well on subsequent follow-ups. Keywords: Unilateral Thyroid Agenesis, Thyroidectomy, Case Report.